Crowdsourcing your sales let your customers sell themselves (and others) - Libert, Barry (FTPress Delivers elements, 2010)
This Element is an excerpt from We Are Smarter Than Me: How to Unleash the Power of Crowds in Your Business (9780132244794) by Barry Libert and Jon Spector. Available in print and digital formats. How to build a crowdsourced, word-of-mouth sales and marketing operation that works! As P & G's Web site boasts, "Three billion times a day P & G brands touch the lives of people around the world." But the company has another, very different line of business. It offers the services of hundreds of thousands of moms and teenagers as word-of-mouth marketers-for its own divisions and those of other organizations as well